ON THE TYPES OF MESOZOIC ARCHOSTEMATAN BEETLES (INSECTA, COLEOPTERA, ARCHOSTEMATA) IN THE NATURAL HISTORY MUSEUM, LONDON - Ponomarenko A.G. (My University, 2006)
About 40 type specimens of archostematan beetles from the Jurassic, Lower Cretaceous, and Paleogene of England, named by P. Brodie, J.O. Westwood, C. Giebel, A. Handlirsch, F. Zeuner, P. Whalley, and R. Crowson and stored in the Paleontological Department of the Natural History Museum (London) are redescribed. Nine genera and 11 species are recognized, three genera are assigned to Archostemata for the first time. One new species, Tersus crowsoni (Schizophoridae), is described.
Keywords: Mesozoic; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская